Pengembangan Pertanian Urban Berkelanjutan Dengan Hidroponik Melalui Program Sosialisasi Di Perkotaan: Hasil Kegiatan KKN Di Kalijudan - Condro Widodo; Zahira Faticatiana Waluyo; Adinda Permata Salsabila; Rezza Alfarizqi; Eries Priandana Putra (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
Surabaya, a city with high population density in East Java, faces challenges in managing land for reforestation. To address this issue, the Surabaya Green and Clean (SGC) Program was introduced, focusing on greening and waste management. One of the proposed solutions is hydroponics, a soilless farming method that can be applied on limited land. On July 28, 2024, community service activities were carried out in Kalijudan Village, Mulyorejo District, Surabaya City, to introduce and increase public knowledge about hydroponics. This activity involved socialization and practical hydroponic planting with the participation of 25 residents. The program consisted of preparation stages, socialization, planting practices, and report preparation. Socialization included exposure to hydroponic theory and practical demonstrations, while each participant received tools and materials for home experiments. The planting method with rockwool has proven effective in supporting plant growth, while the distributed eco-enzyme provided dual benefits by increasing plant growth and reducing household waste. This program successfully introduced hydroponic technology and increased awareness of sustainable urban agriculture. Hopefully, this activity will be the first step in developing hydroponics and creating a greener environment in Surabaya.